El Triatlon y el control de la carga mediante la percepcion del esfuerzo - Mallol, M.; Camara, J.; Calleja-Gonzalez, J.; Yanci, J.; Mejuto, G. (Archivos de medicina del deporte, 2015)
The modern triathlon has become one of the most popular endurance sports Worldwide. Anyway shows specific historical characteristics and on the other hand, biological demands that make it a different sport. Due to its popularity during the last decades, new research methods have been applied to its different modalities and in different aspects. In order to maximize the performance and get the peak performance as prolonged as possible, these investigations have developed new materials for practitioners and improve new training methods, the transitions among modalities during competitions, the training and competitions load control, the big amount of competitions and the best training`s techniques among others. However, not all triathletes have the access to the same training monitoring control as elite triathletes do. Therefore, it could be of great interest for athletes and coaches to develop a valid, reliable and easy managing tool in order to control the training load in as many individuals as possible with reliable accuracy, validity. Thus, it would be relevant to know the main methods of training load and competition load in endurance disciplines sports especially focus on triathlon. Therefore, in the present research work, we will analyze the current concept of triathlon sport and its main methods to set the training work load, internal and external. Thus, we will focus on those methods based on athlete`s own perceived exertion effort (RPE), but previously we will analyze whether current scientific literature (for author`s knowledge) describes those training and competition load methods and their reliability in triathlon.